Dry bones rattling : community building to revitalize American democracy - Warren, Mark R., 1955- (Princeton studies in American politics., 2001)
Dry Bones Rattling offers the first in-depth treatment of how to rebuild the social capital of America's communities while promoting racially inclusive, democratic participation. The Industrial Areas Foundation (IAF) network in Texas and the Southwest is gaining national attention as a model for reviving democratic life in the inner city--and beyond. This richly drawn study shows how the IAF network works with religious congregations and other community-based institutions to cultivate the participation and leadership of Americans most left out of our elite-centered politics. Interfaith leaders from poor communities of color collaborate with those from more affluent communities to build organizations with the power to construct affordable housing, create job-training programs, improve schools, expand public services, and increase neighborhood safety.